West Java Regional Cultural Management UPTD in Designing Virtual Art Performances During the COVID-19 Pandemic - Novianti Eka Kartika; Dasrun Hidayat (Kanal: Jurnal Ilmu Komunikasi, 2021)
Virtual art performances are a form of program during the pandemic by the West Java Regional Cultural Management UPTD in the use of social media on YouTube. The purpose of this study was to determine the design of the virtual art performance program starting from the initial analysis stage, the production stage to the post-production by the executor of the West Java Regional Cultural Management UPTD. This research uses qualitative research with ethnographic study of public relations. This study aims to examine the behavior of public relations (PR) communication carried out by virtual art performers in collaboration with artists to carry out virtual art performances. The results of this study indicate that there are stages of the virtual art performance program, starting from the stage of situation analysis, determining the goals and objectives of the program. The stages during production are holding virtual art performances and post-production such as editing and uploading to YouTube media. Therefore, this study uses the relevant model, namely The IPPAR (Insight, Strategic Program, Program Implementation, Action and Reputation) mode in the process of virtual art performances.